Produits chimiques : les seuils de tolérance - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Écotoxicologie appliquée GTZ, 2000 Distribution : Margraf Verlag BP 1205 D-97985 Weikersheim, Allemagne Fax : + 49 (0) 79 34 81 56 E-mail : margraf@compuserve.com 326 pages ISBN 3-8236-1336-7 Prix : 14 $ US • 15, 72